The role of Internal Audit in reducing Financial Risks (Applying to Companies listed in the Saudi Stock Exchange) - Abdelrahim, Elsamani Ataelmanan; Abbu, Mai Osman Ali (Journal of Economic, Administrative and Legal Sciences, 2025)
The researcher addressed the role of internal audit in reducing financial risks. The study aimed to identify the extent of the contribution of the internal audit department in reducing financial risks, and to identify the obstacles that reduce its contribution to reducing financial risks. The study problem was represented in the following questions: Does the internal audit department contribute to reducing financial risks? And does the internal audit department face obstacles that limit its contribution to reducing financial risks? To achieve the objectives of the study and find objective solutions to its problem, the researcher assumed that the internal audit department contributes to reducing financial risks, and that there are no obstacles that reduce the contribution of the internal audit department in reducing financial risks. The researcher used the descriptive analytical approach, in addition to using many appropriate statistical methods, including the Statistical Package for the Social Sciences (SPSS). After testing the hypotheses, the validity of the first hypothesis was found (the internal audit department contributes to reducing financial risks), and the validity of the second hypothesis (the internal audit department does not face any obstacles that reduce its contribution to reducing financial risks). The researcher recommended supporting the internal audit department by providing it with an appropriate organizational position, in addition to providing the appropriate material and human capabilities so that it can perform its mission and achieve its goals with high efficiency.